3D multiscale analysis method for explosion problems based on the substructure of the explosion source. (1st February 2022) - Bao, Xin; Li, Shutao; Liu, Jingbo; Chen, Yeqing
Highlights: We present a new 3D multiscale analysis method for explosion problems. The proposed method reduces the calculation cost while ensuring accuracy. The standard explosion loads for a given explosion equivalent can be obtained. Abstract: When using the explicit finite element method to solve explosion problems at engineering sites, high-density meshes are usually adopted near the explosion source to calculate the high-frequency components of the explosion response. However, the critical time step in an explicit algorithm is usually controlled by the minimum mesh size. The resulting poor computational efficiency will restrain the application of the overall explosion source-engineering site model in explosion problems for large-scale numerical systems, especially in 3D conditions. In this study, a 3D multiscale analysis method based on the substructure of explosion sources is proposed. This method computationally separates the process of explosion initiation and the propagation of shock waves by dividing the model of engineering sites under explosion loads into a small-scale near-source model and a large-scale site-structure model, and the substructure of explosion source is used as an approach for explosion action transmission and mesh transition between different models, thereby progressively completing the explosion analysis of the entire explosion source-site-structure system from the near-source region to the far-field region. The proposed multiscale method adopts appropriate mesh sizes and numerical techniques in different calculation stages and avoids the use of irregularly shaped elements that are employed in traditional mesh transition methods, thereby reducing the calculation cost and modeling difficulties while ensuring accuracy. In addition, the proposed method provides a convenient approach for calculating standard explosion loads for a given explosion equivalent, which can be further applied in multiload-case explosion response analyses of large-scale complex site-structure systems.